2023
DOI: 10.1002/bit.28606
|View full text |Cite
|
Sign up to set email alerts
|

Brain organoids: A revolutionary tool for modeling neurological disorders and development of therapeutics

Prabha Acharya,
Na Young Choi,
Sunil Shrestha
et al.

Abstract: Brain organoids are self‐organized, three‐dimensional (3D) aggregates derived from pluripotent stem cells that have cell types and cellular architectures resembling those of the developing human brain. The current understanding of human brain developmental processes and neurological disorders has advanced significantly with the introduction of this in vitro model. Brain organoids serve as a translational link between two‐dimensional (2D) cultures and in vivo models which imitate the neural tube formation at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…Research based on data from birth cohorts has revealed that when individuals are exposed to endocrine disruptors during crucial stages of neurodevelopment, it can have detrimental effects on various cognitive functions, such as memory and language, as well as attention, emotions, and social behaviors [ 80 , 81 ]. Immortalized human neural progenitor cells (hNPCs) cultivated as three-dimensional floating spheres can represent processes of brain development [ 82 , 83 ]. After exposition to potential endocrine disruptors, the process of NPC proliferation can be studied [ 84 , 85 ].…”
Section: Need For New Methodsmentioning
confidence: 99%
“…Research based on data from birth cohorts has revealed that when individuals are exposed to endocrine disruptors during crucial stages of neurodevelopment, it can have detrimental effects on various cognitive functions, such as memory and language, as well as attention, emotions, and social behaviors [ 80 , 81 ]. Immortalized human neural progenitor cells (hNPCs) cultivated as three-dimensional floating spheres can represent processes of brain development [ 82 , 83 ]. After exposition to potential endocrine disruptors, the process of NPC proliferation can be studied [ 84 , 85 ].…”
Section: Need For New Methodsmentioning
confidence: 99%
“…Other important experimental models for the ZIKV-AD hypothesis would be human-induced pluripotent stem cell (hiPSC)-derived three-dimensional (3D) cultures like brain organoids and spherical self-organized aggregates or hiPSC-derived neurological/immunoregulatory cells [ 92 ]. These models have been widely used for drug repurposing.…”
Section: Elaboration Of Selected Viral Examples Implicated In Ad and ...mentioning
confidence: 99%
“…Organoid models of various neurodegenerative and neurodevelopmental disorders 72 , including Alzheimer's disease, Parkinson's disease, and autistic spectrum disorders, also present opportunities for drug testing. Advancements in generating CNS barrier-forming organoids (CBFOs) contribute to drug permeability testing for CNS drug development.…”
Section: Human Brain Organoids In Drugmentioning
confidence: 99%